INTERNALISASI NILAI TANGGUNG JAWAB PADA SISWA SMA NEGERI 1 AJIBARANG - Khafifah Andriani (Universitas Hamzanwadi, 2021)
This study aims to describe the attitude of responsibility for students of SMA Negeri 1 Ajibarang, forms of responsibility, and the factors that influence responsible behaviour. Researchers used descriptive research methods with a phenomenological approach. Based on the results of research and discussion, it shows that: 1) responsibility is a duty and obligation that must be carried out by students while in school, and most of the students of SMA Negeri 1 Ajibarang can fulfil their responsibilities well. 2) the form of student responsibility at school includes the responsibility to God (performing midday prayers at school), oneself (arriving on time, attending lessons in an orderly manner, always doing the tasks assigned by the teacher, carrying out daily pickets), and fellow citizens school (greeting, greeting when meeting the teacher, asking permission from the teacher if there is a need during class). 3) Influencing factors include teachers who become role models, school facilities, habituation to do assignments during open hours, and habituation through 30 minutes activities with SMAN 1 Ajibarang.